Analysis of Cost-Effectiveness of Antihypertensive Therapy in Hypertension Patients at Al-Ihsan Regional Public Hospital in 2023 - Isnaini, Masyitah; Widiarti, Widiah; Khairinisa, Miski A. (Universitas Padjadjaran, Indonesia, 2024)
Hypertension is a disease that causes an abnormal increase in blood pressure, which causes cardiovascular disease. Long-term hypertension therapy requires large costs. Apart from that, existing antihypertensives are also very varied, so a cost-effectiveness analysis is needed in order to choose medications that balance costs and advantages. This study aims to determine the most economical antihypertensive medication at Al-Ihsan Regional Public Hospital in Baleendah. Based on patient medical records, this study was carried out retrospectively. Therapy data and treatment costs are the basis for the data collection process. The data is processed descriptively. The reduction in blood pressure that meets the target and the length of stay (LOS) is used to determine how effective the therapy was; the ACER and ICER values are used to determine how cost-effective the procedure was. According to the research findings, the average total cost of group A (ACEI with CCB) is IDR 2,311,000.00, whereas group B (ARB with CCB) is IDR 2,888,823.00. The efficacy of group A (ACEI with CCB) was 83.3%, while group B (ARB with CCB) was 52.4%. The findings showed that among inpatient hypertension patients at Al-Ihsan Regional Public Hospital, group A (ACEI with CCB) was more cost-effective, with an Average Cost Effectiveness Ratio (ACER) value of IDR 27,743,097, than group B (ARB with CCB ACER value of IDR 55,130,209). Based on this study, therapy of group A (ACEI with CCB) offers excellent therapeutic efficacy at a reduced cost. Hospitals are expected to have the ability to handle their spending on hypertension medications appropriately and efficiently.